Análise espacial de sífilis em gestante e congênita no estado do Paraná: ênfase na região de fronteira - Ramos , Sirlei (2021)
INTRODUCTION: Syphilis is a sexually transmitted infection of concern. In Brazil, it is understood as a public health problem. Although it has a relatively simple and inexpensive treatment that can be prevented, its incidence is increasing. OBJECTIVE: To analyze the cases of syphilis in pregnant women (SG) and congenital (CS) in the state of Paraná, with emphasis on the border region. METHODOLOGY: This is an observational study of an ecological type: a spatial analysis of the distribution of cases of Syphilis in Pregnant Women (SG) and Congenital Syphilis (SC) in the municipalities of the state of Paraná, from 2010 to 2018. The collection data occurred in the National System of Diseases and Notifications - SINAN of the Ministry of Health, on the Datasus page, data referring to congenital syphilis and syphilis in pregnant women were analyzed. Data analysis was carried out through a survey conducted through a descriptive statistical analysis and from the municipal rates for the incidence of gestational and congenital syphilis. RESULTS: From the period evaluated, the annual rate for SG was 11.0/10 thousand, while for SC it was 37.89/100 thousand. In the analyzed border region, the rate of syphilis in pregnant women presents a significant difference, when comparing the border municipalities whose incidence is equivalent to 10.25/10 thousand; in other municipalities outside the border, the data cover 7.32 /10 thousand, p<0.001). The number of cases of congenital syphilis on the border is also higher compared to other municipalities. In SG it is possible to observe high rates concentrated in the west, southwest, metropolitan and coastal regions, in the northern region of the state there are several cities with high rates, but they do not present concentration. The municipal rates of SC, on the other hand, are high in all regions, but concentrated in coastal, metropolitan, southern and part of the western, northern and northwestern regions of the state. CONCLUSION: Both syphilis rates in pregnant women and congenital syphilis increased during the study period. Both infections are spatially dependent. The research concluded that prevention and assistance actions are needed to interrupt the disease\transmission cycle.